Penguatan Ketahanan Generasi Muda terhadap Ancaman Judi Online dan Pinjaman Online melalui Sosialisasi Peraturan Daerah Kabupaten Sukoharjo Nomor 13 Tahun 2024 - Marisa Kurnianingsih; Fahmi Fairuzzaman; Andria Luhur Prakoso; Kuswardhani Kuswardhani (CV. BImbingan Belajar Assyfa, 2026)
The rapid advancement of digital technology has provided numerous benefits to society while simultaneously increasing the risk of online gambling and illegal online lending, particularly among young people. Limited legal literacy, digital literacy, and financial literacy have become significant factors contributing to the vulnerability of youth to these forms of digital crime. This community service program aimed to strengthen the resilience of young people against the threats of online gambling and illegal online lending through the dissemination of Sukoharjo Regency Regional Regulation Number 13 of 2024 concerning Youth Development and Empowerment. The program employed a participatory legal education approach consisting of lectures, interactive discussions, and question-and-answer sessions. The program was evaluated qualitatively through observations of participants' engagement, discussion dynamics, and feedback during the activities without utilizing pre-test or post-test instruments. The results indicate that the legal education program enhanced participants' understanding of the legal, social, and economic impacts of online gambling and illegal online lending while fostering greater awareness of the importance of legal literacy, digital literacy, financial literacy, and access to legal aid as preventive measures. Furthermore, the dissemination of Sukoharjo Regency Regional Regulation Number 13 of 2024 strengthened participants' understanding of the importance of character development and youth resilience in addressing challenges in the digital era. Overall, the findings demonstrate that legal education serves as an effective strategy for promoting legal awareness and strengthening youth resilience through collaboration among higher education institutions, local government, and the community.